METHODOLOGY OF COST RECORDING AND ACCOUNTING IN DAIRY COOPERATIVES - Marzena Ganc; Mirosław Wasilewski (Polityki Europejskie, Finanse i Marketing)
The purpose of the research is to present the theoretical and practical aspects of determining the unit cost of producing dairy products in what is defined as a "typical" dairy cooperative. The Euclideanand urban distance method was used to determine a typical object with n = 88 dairy cooperatives – the following set of variables was defined, which are common to all cooperatives and reflect the sizeand specificity of cooperative units on the milk market in Poland. The selected cooperative provides a procedure for calculating the unit costs of dairy products on the basis of a detailed case study. Thefull cost account used in cooperatives does not provide cost information for management decisions.Indirect cost accounting using contractual factors does not provide reliable cost data. An important issue in determining the coefficients is the adoption of a measure which reflects the actualrelationship between cost and cost carrier, a product which, in the case of dairy products, may be difficult. It would be appropriate to attempt to introduce a variable cost account in dairy cooperativesin order to avoid the contractual assignment of indirect costs to products. The main problem highlighted by the authors is the lack of an adequate information system for the cost accounting indairy cooperatives. The implementation of such solutions would allow managers of a dairy cooperative to make appropriate (short-term) decisions in terms of developing an assortmentstructure based on data e.g. on profitability at the level of individual products.